The Influence of Realistic Mathematics Education on the Mathematical Problem-Solving Ability and Learning Independence of Class V Students at Jarakan State Elementary Schools - Yuniartika, Shani; Trisniawati, T; Anggreini, Dewi; Silvianti, Fitrilia (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to describe the influence of the realistic mathematic education approach model on students' mathematical problem-solving abilities and define the impact of the realistic mathematic education approach on students' learning independence. The sample used in this research was the VA and VB classes of Jarakan State Elementary School, with 35 students in each class. This type of research is quasi-experimental research. The instruments used in this research were test questions on students' mathematical problem-solving abilities and learning independence questionnaires. The research test carried out by the researcher used a significance level of 5% so that if the significance value is less than 0.05, it can be concluded that the realistic mathematic education approach positively affects students' mathematical problem-solving abilities. The learning independence test can be seen by comparing the total score, mean value, and percentage of the level of student response contained in the descriptive statistical analysis. If the score, mean, and percentage of student response level percentage of the experimental class are higher than the control class, it can be concluded that the realistic mathematic education approach has a positive influence on student learning independence.